(untitled) (Research, Society and Development, 2021)
This study aimed to assess the prevalence of the main bacteria found in urocultures that cause UTI in patients seen in hospitals in different Brazilian states, as well as the profile of bacterial resistance and sensitivity to antimicrobials, by searching an updated database, promoting a review of the proposed theme. In order to carry out this study of literary review, a search for recent articles (up to 7 years after publication) was carried out in the databases of electronic periodical Pubmed, Medline, Lilacs e Scielo, with availability of complete texts for the collection of data containing the main bacteria found in the urocultures of patients with Urinary Tract Infections along with their resistance to the most diverse types of antibiotics. Articles published between 2014 and 2020 that addressed the main bacteria found in urine cultures and their antimicrobial resistance profile were included. With exclusion criteria, any article that does not deal with any of the themes mentioned above and that has been published outside the defined chronological time. 4,173 positive urocultures were found with the microorganism most frequently isolated to Escherichia coli, followed by Klebsiella pneumoniae and Proteus mirabilis. It was possible to check high levels of resistance to E. coli for some antimicrobials of first choice for the treatment of UTI, such as ampicillin (55.32%) and sulfamethoxazole + trimetroprim (34.36%). These data collected through an updated database demonstrate the need to promote knowledge about this infection in order to define an appropriate empirical therapy, thus creating a therapeutic scheme that will assist health professionals during the treatment of patients with UTI.